Dental caries in children with Down syndrome and associated factors - Lina Naomi HASHIZUME; Mauricio José Santos MOREIRA; Juliana Balbinot HILGERT (RGO: Revista Gaúcha de Odontologia, 2021)
ABSTRACT Objective: The aim of this study was to assess dental caries and associated factors in children with Down syndrome (DS). Methods: The sample consisted of children between 6 and 12 years old being 67 with DS and 46 without DS. Caries experience and gingival bleeding index were recorded. Questionnaire with socio-demographic questions was applied to children’s caregivers. Crude and adjusted prevalence ratios for caries in primary and permanent teeth were calculated by means of Poisson regression with robust variance. Results: Children with DS and without DS showed similar results for caries experience. Only age was associated with caries at permanent teeth. None of the variables were associated with caries at primary teeth in both groups of children. Conclusion: It can be concluded that social factors and access to dental services analyzed in this study were not associated with dental caries in children with DS syndrome. Furthermore, caries experience for children with DS and those without the syndrome were not different based on this study.